Analysis of deformation behavior in circular and square hollow sections with wall thickness of 0.7 -1.0 mm in rotary draw bending - Widodo, Syamsul Bahri; Suheri, Suheri; Sabri, Faris Ahmad Mizanus; Arif, Zainal; Raziqin, Muhammad Khairul; Menazmi, Teuku; Safi'i, Muhammad (Jurnal Polimesin, 2025)
Precise control of tube deformation during rotary draw bending is critical for automotive, structural, and piping applications to avoid rework and scrap. This study investigates the deformation behavior of circular (CHS) and square (SHS) tubes during rotary draw bending to provide practical guidelines for defect-free manufacturing. This study investigates the deformation behavior of circular hollow section (CHS) and square hollow section (SHS) tubes during rotary draw bending, focusing on springback, ovalization, and wrinkling phenomena. The experimental specimens consisted of ASTM A36 tubes: circular hollow sections (CHS) with an outer diameter of Ø25 mm and square hollow sections (SHS) with a nominal cross-section of 25 × 25 mm. Each geometry was tested at wall thicknesses of 0.7, 0.8, and 1.0 mm. The specimens were bent at angles of 30°, 60°, and 90° under controlled conditions. Experimental results reveal that CHS consistently exhibits lower springback (≈ 2.5–5.0°) and ovalization (≈ 7–14%) than SHS, which reached up to 7.0° springback and 16.6% ovalization. Wrinkling defects were observed exclusively in SHS, occurring in 100% of specimens at 90° with 0.7–0.8 mm wall thickness. ANOVA confirmed tube geometry as the dominant parameter (F = 764, p 0.001), followed by bending angle and wall thickness, with no significant interactions. Unlike prior studies analyzing CHS or SHS individually, this work provides a systematic comparison under identical conditions, bridging experimental validation with practical guidelines. The findings highlight the decisive role of cross-sectional geometry in tube bending mechanics and suggest minimum thickness thresholds and compensatory tooling strategies for defect-free manufacturing.